2020
DOI: 10.1007/s00330-020-06666-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics of computed tomography and magnetic resonance imaging in renal cell carcinoma—a systematic review and meta-analysis

Abstract: Objectives (1) To assess the methodological quality of radiomics studies investigating histological subtypes, therapy response, and survival in patients with renal cell carcinoma (RCC) and (2) to determine the risk of bias in these radiomics studies. Methods In this systematic review, literature published since 2000 on radiomics in RCC was included and assessed for methodological quality using the Radiomics Quality Score. The risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 29 publications
(33 reference statements)
4
87
0
1
Order By: Relevance
“…Furthermore, most researchers do not offer details regarding preprocessing steps and model parameters. Only a few authors made their code publicly available in a repository [40]. This lack of detailed information hampers the reproducibility of the results, makes it difficult to compare methods, and does not help in pushing this field forward.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most researchers do not offer details regarding preprocessing steps and model parameters. Only a few authors made their code publicly available in a repository [40]. This lack of detailed information hampers the reproducibility of the results, makes it difficult to compare methods, and does not help in pushing this field forward.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that renal masses including RCC subtypes, AMLwvf, and oncocytomas can be portrayed with distinct gray-level imaging patterns that are traceable by radiomic analysis [15]. Radiomics includes a number of approaches designed to convert medical images to quantitative, minable, and high-dimensional data [3]. Machine (ML) and deep learning (DL) algorithms are used to automatically extract and analyze histogram, texture, and shape information from imaging data which may not be evident to the naked eye.…”
Section: Renal Mass Differentiationmentioning
confidence: 99%
“…However, despite its extensive use in research and favorable results linking CT/MRI texture features to renal mass characterization, the routine use of radiomics in clinical practice is yet to be seen. For imaging markers, including texture-based metrics, to bridge the translational gap between an experimental research tool and a clinically applicable diagnostic algorithm, its technical and biological validity, biological validity, qualification, and cost-effectiveness need to firstly be established [3] and was identified as a promising CDS tool for renal mass identification [17]. Similarly, Erdim et al compared eight ML algorithms to construct a prediction model for renal mass diagnosis based on CECT imaging from both benign and malignant lesions.…”
Section: Renal Mass Differentiationmentioning
confidence: 99%
See 2 more Smart Citations